Answer:
Explanation:
X^2-3x=7/4 should first be rewritten in standard form, which here would be:
x^2 - 3x - 7/4 = 0.
1. Identify the coefficient of the x term and take half of that number:
-3/2
2. square this result: (-3/2)^2 = 9/4
3. add this last result, 9/4, between the -3x term and the -7/4 term, and then subtract it as shown:
x^2 - 3x + 9/4 - 9/4 - 7/4 = 0
4. Rewriting the first 3 terms as the square of a binomial, we get:
(x - 3/2)^2 - 16/4 = 0, or (x - 3/2)^2 = 16/4
5. Take the square root of both sides, obtaining:
x - 3/2 = ±√4/2 or ±√2
6. Write out the two roots: x = 3/2 + √2
and x = 3/2 - √2